2011
DOI: 10.1167/iovs.10-6264
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Primary Open-Angle Glaucoma and Motor Vehicle Collisions

Abstract: Advanced POAG with marked visual field defects may be a risk factor for MVCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 32 publications
2
45
1
1
Order By: Relevance
“…Glaucoma negatively effects driving performance (Crabb et al, 2013;Tanabe, 2011;Kwon, 2016;Owsley et al, 1998;Haymes, 2008). The links between reports of visual experience (Crabb et al, 2013;Hoste, 2003) and physiological effects of optic neuropathy and visual field loss are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma negatively effects driving performance (Crabb et al, 2013;Tanabe, 2011;Kwon, 2016;Owsley et al, 1998;Haymes, 2008). The links between reports of visual experience (Crabb et al, 2013;Hoste, 2003) and physiological effects of optic neuropathy and visual field loss are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies Szlyk et al 12,13 compared drivers with and without glaucoma with respect to simulator and self-reported MVCs and reported in one instance no difference 13 and a higher frequency of both events in the other. 14 Observational studies have also yielded inconsistent findings with some studies reporting no association 15,16 between glaucoma and MVC occurrence and others reporting a positive association 17-19 In one study, glaucoma was protective for MVCs, 20 which might imply that glaucomatous drivers exercise greater cautiousness when behind the wheel. In a subsequent report we demonstrated that glaucomatous drivers with moderate to severe visual field impairment in the worse eye had an increased risk for MVC involvement and at-fault MVCs compared to glaucomatous drivers with no defect.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 However, it is also important to bear in mind that the methodology used in previous studies was wide ranging including, for example, both police- 16-18,20,21 and self-reported MVCs, 12,13,15,19 as well as clinically confirmed and self-reported glaucoma. 17 Additionally, disagreement among prior studies may stem from some studies not accounting for driving exposure when assessing crash risk 22 and limited sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…17 A history of glaucoma in males was also a significant predictor of increased crash risk in older drivers. 51 Tanabe et al 30 found that self-reported motor vehicle collisions were significantly higher in drivers with severe primary openangle glaucoma and extensive visual field impairment. This is consistent with previous research by Haymes et al, 17 where glaucoma patients were 5 times more likely to be involved in a motor vehicle collision and 10 times more likely to be fault.…”
Section: Glaucoma and Crash Riskmentioning
confidence: 99%
“…In addition, many previous studies did not adjust for comorbidities, had small sample sizes 53 or used self-reported information. 30 …”
Section: Glaucoma and Crash Riskmentioning
confidence: 99%